In‐hospital costs associated with chronic constipation in Belgium: a retrospective database study. Issue 3 (11th December 2013) - Chevalier, P.; Lamotte, M.; Joseph, A.; Dubois, D.; Boeckxstaens, G.
Abstract Background Real‐life data on the economic burden of chronic idiopathic constipation are scarce. The objectives of this study were to assess hospitalization resource use and costs associated with chronic constipation and its complications in Belgium. Methods This was a single country, retrospective study using the IMS Hospital Disease Database (2008), which comprises data on 34% of acute hospital beds in Belgium and contains information on patient demographics, length of stay (LOS), billed costs, drug use, diagnoses, and procedures. Stays with a primary diagnosis of constipation, or a secondary diagnosis of constipation and a concomitant diagnosis of a constipation‐related complication, were selected. Patients with diagnoses of colorectal cancer, ulcerative colitis or Crohn's disease, or who had stays involving potentially constipation‐inducing procedures, were excluded as having secondary constipation. Patients receiving opioids, calcium‐antagonists, antipsychotics or antidepressants were excluded as having drug‐induced constipation. Key Results In total, 1541 eligible patients were identified. The average unadjusted cost per day in hospital for idiopathic constipation was €441 (€311 ± 1.4 in day clinic visits without overnight stays; €711 ± 14.0 in full hospitalizations with complications). The average LOS in a full hospitalization setting was 7.0 and 4.0 days in stays with and without complications, respectively. The most frequent drug and procedural treatments were osmotically acting laxatives (with complications: 42.61%; without complications: 35.69%), and transanal enema (2.32% and 2.03%), respectively. Conclusions & Inferences The burden of constipation is often underestimated; it is a condition reflected by hospital‐related costs comparable to such indications as migraine, which increase when associated with complications.